2017
DOI: 10.1021/acsomega.7b00700
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Catalysis at Nanoscale: Enzyme-Coated Nanoparticles as Colloidal Biocatalysts for Polymerization Reactions

Abstract: Enzyme-catalyzed controlled radical polymerization represents a powerful approach for the polymerization of a wide variety of water-soluble monomers. However, in such an enzyme-based polymerization system, the macromolecular catalyst (i.e., enzyme) has to be separated from the polymer product. Here, we present a compelling approach for the separation of the two macromolecular species, by taking the catalyst out of the molecular domain and locating it in the colloidal domain, ensuring quasi-homogeneous catalysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…Leaching of the enzymes was not observed due to their strong interactions to the gold surface. This was demonstrated by the absence of enzymatic activity in the supernatant after multiple centrifugation and redispersion cycles . The enzymes can catalyze chemical reactions in aqueous solutions, after they have been immobilized to the nanocarriers.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…Leaching of the enzymes was not observed due to their strong interactions to the gold surface. This was demonstrated by the absence of enzymatic activity in the supernatant after multiple centrifugation and redispersion cycles . The enzymes can catalyze chemical reactions in aqueous solutions, after they have been immobilized to the nanocarriers.…”
Section: Introductionmentioning
confidence: 70%
“…The enzyme is then robustly attached to the scaffold and remains catalytically active. This is in accordance with prior studies, where we showed the robust binding of enzymes and other proteins to metal nanoparticles (gold, iron oxide) via a simple ligand exchange reaction. The reaction is mainly driven by the displacement of small molecules (citrate) by the macromolecular proteins on the particle surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…GNPs are a popular support for enzyme immobilization due to its easy size‐controlled preparation and good biocompatibility. Besides, various flexible bioconjugation strategies of GNPs with enzymes have been proposed and sample processing is straightforward . A variety of strategies has been used for enzyme immobilization such as adsorption ionic binding , affinity binding and covalent binding.…”
Section: Gnps In Sample Preparationmentioning
confidence: 99%